2012
DOI: 10.1002/art.34560
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab mediates loss of CD19 on B cells in the absence of cell death

Abstract: Objective To evaluate loss of the B cell specific marker CD19 with addition of rituximab (RTX) to healthy donor blood and to determine the role of complement mediated cytotoxicity in these cells. Methods Healthy donor whole blood and peripheral blood mononuclear cells (PBMC) were evaluated for loss of CD19 in the presence of RTX using flow cytometry. The effect of complement on CD19 loss was examined using serum free media, C3- and C5- deficient sera, and a C5 blocking antibody. Evidence for B cell death was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 23 publications
(42 reference statements)
5
47
1
Order By: Relevance
“…Both hRFB4, a humanized anti-CD22 mAb that binds to a different epitope than epratuzumab, and hA19 also mediate trogocytosis of multiple B-cell proteins, as shown here. In the present study, we confirmed the ex vivo reduction of CD19 on B cells in PBMCs by rituximab, 41 which also mediated trogocytosis of CD21, CD79b, and CD22. Except for CD22, each antigen was reduced more by rituximab than epratuzumab, likely due to the ;10-fold higher expression of CD20 compared with CD22, wherein the latter is also more rapidly internalized upon antibody ligation, 8,9 and internalization is expected to compete with trogocytosis.…”
Section: Discussionsupporting
confidence: 76%
“…Both hRFB4, a humanized anti-CD22 mAb that binds to a different epitope than epratuzumab, and hA19 also mediate trogocytosis of multiple B-cell proteins, as shown here. In the present study, we confirmed the ex vivo reduction of CD19 on B cells in PBMCs by rituximab, 41 which also mediated trogocytosis of CD21, CD79b, and CD22. Except for CD22, each antigen was reduced more by rituximab than epratuzumab, likely due to the ;10-fold higher expression of CD20 compared with CD22, wherein the latter is also more rapidly internalized upon antibody ligation, 8,9 and internalization is expected to compete with trogocytosis.…”
Section: Discussionsupporting
confidence: 76%
“…Many of our findings of trogocytosis and effector function exhaustion with respect to CD20 mAbs in CLL have been replicated and extended, in some cases to other mAb-antigen pairs, in the clinic and in the laboratory Jones et al, 2012;Masuda et al, 2013;Rossi et al, 2013;Baig et al, 2014). Therefore, the implications of these studies with respect to use of CD20 mAbs may also pertain to other mAbs currently used to treat cancer.…”
Section: Possible Generalization To Othermentioning
confidence: 83%
“…We read with great interest the article by Jones et al in which they reported that measurement of CD19ϩ cells as a marker of rituximab (RTX)-induced B cell depletion might be flawed (1). The authors noted that the addition of RTX to healthy donor peripheral blood mononuclear cells (PBMCs) in vitro resulted in a loss of CD19 expression on B cells in the absence of cell death.…”
Section: To the Editormentioning
confidence: 99%